THE IMPACT OF NON-STANDARD ENGLISH ON ACADEMIC AND PROFESSIONAL COMMUNICATION - Janardhanan, Prathyaksh; Jayathilakan, Hidha; Mangalaraj; Niranjanadevi; Singh, Shiv Veer (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The growing international application of the English language has given rise to various types of English that is generally referred to as non-standard English. The research question of this research was as follows: How does non-standard English affect the effectiveness of communication in an academic and professional setting? A combination of both qualitative and quantitative strategies was used, where 120 individuals were chosen with different linguistic and professional backgrounds. Respondents rated written documents in standard and non-standard versions and they were rated based on their clarity, credibility, and professionalism. Also, qualitative data were collected to examine the latent attitudes toward language variation. The result showed that non-standard English was not a significant factor in influencing the understanding because the participants could normally comprehend both types of communication. There were, however, significant variations in the evaluative perceptions with standard English always rating higher in respect to credibility and professionalism. There were mixed attitudes as well, with participants balanced between awareness of linguistic diversity and adherence to traditional norms in a formal context. The research outlines the difference between the effectiveness in communication and social perception, and the view that language judgments are not merely based on the clarity, but also on institutional expectations which are deeply rooted. These findings assert the necessity of ensuring the growth of sensibility towards linguistic diversity and the simultaneous persistence of effective communication initiatives in academic and work settings.